Interventions to Improve the Quality of Life of Thyroid Cancer Patients : A Scoping Review - Asroful Hulam Zamroni; Elvi Kurnia Damayanti; Fachril Ismail; Lisa Isdaryanti; Rizky Nur Azhadin; Yulis Setiya Dewi (Indonesian Journal of Global Health Research, 2025)
Thyroid cancer treatment can cause side effects that have a significant impact on the patient's quality of life and health, so effective interventions are needed to address these impacts. This study aimed to explore various interventions, their impact on the quality of life of thyroid cancer patients. This study used a scoping review approach with PRISMA-ScR for article selection. Articles were obtained from Scopus, PubMed, ScienceDirect, and ProQuest databases published between 2016 and 2024 using keywords related to thyroid cancer, quality of life, intervention and therapy. Of the initial 2043 articles, 9 articles met the inclusion and exclusion criteria. The extracted data was analyzed using qualitative methods with identified were author, year of publication, research design, country, type of intervention, duration of intervention, research results, and JBI. The results of the analysis revealed three types of interventions in improving the quality of life of patients with thyroid cancer: (1) Psychological with mindfulness therapy, memory therapy, psychological nursing intervention, behavioral intervention, and technology-based therapy (mHealth); and (2) Physical with Progressive Muscle Relaxation (PMR), and home-based physical exercise (aerobics, resistance, flexibility). These findings underscore the benefits of interventions to improve the quality of life of thyroid cancer patients which include physical, psychological, and technology-based approaches.